The role of information technology in improving the performance of village owned enterprises - Udin Suadma; Gema Ika Sari; Tata Rustandi (Lentera Negeri, 2026)
This study examines the role of information technology (IT) in improving the performance of rural enterprises, with a specific focus on Village-Owned Enterprises (BUMDes) in Banten Province, Indonesia. While digital transformation has reshaped business practices, many rural enterprises continue to rely on manual systems, limiting efficiency, transparency, and competitiveness. This study adopts a qualitative narrative literature review approach to synthesize existing knowledge on IT adoption and organizational performance in rural enterprise contexts. The review draws on approximately 30–40 academic sources published between 2014 and 2026, including peer-reviewed journal articles, books, and institutional reports retrieved from databases such as Google Scholar, Scopus, and SINTA. Data were analyzed using content and thematic analysis to identify recurring patterns and conceptual relationships. The review identifies four dominant themes linking IT adoption to rural enterprise performance: operational efficiency, data-informed decision-making, financial transparency, and business competitiveness. Rather than providing direct empirical evidence, this study integrates prior findings to develop a conceptual framework that explains how IT contributes to performance improvement under varying levels of digital readiness. The study contributes by offering a synthesized and integrative perspective on IT adoption in rural enterprises and by proposing a framework that highlights the roles of digital literacy, infrastructure readiness, and institutional support as enabling conditions. However, as a literature-based review, this study does not establish causal relationships and should be interpreted as a conceptual foundation that requires further empirical validation.